2019
DOI: 10.3791/58804
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mouse and Human Antibody Repertoires by Next-Generation Sequencing

Abstract: The immense adaptability of antigen recognition by antibodies is the basis of the acquired immune system. Despite our understanding of the molecular mechanisms underlying the production of the vast repertoire of antibodies by the acquired immune systems, it has not yet been possible to arrive at a global view of a complete antibody repertoire. In particular, B cell repertoires have been regarded as a black box because of their astronomical number of antibody clones. However, next-generation sequencing technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In particular, it was found that BDNF mRNA expression could be a biological marker indicating the severity of executive dysfunctions in patients with substance-use disorders (Anders et al, 2020). Similarly, spleen has been used as representative immune organ in mice in the same way as the use of peripheral blood mononuclear cells in humans (Sun et al, 2019). In sense, we found that HFD feeding induces cognitive alterations related to a decrease in BDNF mRNA expression in spleen.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 57%
“…In particular, it was found that BDNF mRNA expression could be a biological marker indicating the severity of executive dysfunctions in patients with substance-use disorders (Anders et al, 2020). Similarly, spleen has been used as representative immune organ in mice in the same way as the use of peripheral blood mononuclear cells in humans (Sun et al, 2019). In sense, we found that HFD feeding induces cognitive alterations related to a decrease in BDNF mRNA expression in spleen.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 57%
“…For library prep, we developed an adapted 5’ rapid amplification of cDNA ends (5’RACE) approach (Fig 1B) 27, 28, 29, 30, 31, 32, 33 , which is simple, unbiased, and requires only minimal amounts of material 27 . We improved the protocol by incorporating features for high-quality and accurate repertoire sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…We adopted a 5’ rapid amplification of cDNA ends (5’RACE) approach for library prep (Fig. 1B) 27, 28, 29, 30, 31, 32, 33 . cDNA synthesis was done with two primers, forward template switching oligos (TSO) with unique molecular identifiers (UMI) /5Biosg/-GTCAGATGTGTATAAGAGACAGNNHATTNNHNNATTNNCGATAGrGrGrG-3’ and reverse 5’- GTGTCACGTACAGAGTCATC(T) 30 VN-3’.…”
Section: Methodsmentioning
confidence: 99%